2015
DOI: 10.2320/matertrans.m2014363
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Dynamics Analysis of the Microstructure of the CaO-P<sub>2</sub>O<sub>5</sub>-SiO<sub>2</sub> Slag System with Varying P<sub>2</sub>O<sub>5</sub>/SiO<sub>2</sub> Ratios

Abstract: The structures of the CaO-P 2 O 5 -SiO 2 slag system with varying P 2 O 5 /SiO 2 ratios at a fixed CaO content have been investigated by molecular dynamics simulation using the pairwise potential model. The results showed that the average bond lengths of Si-O and P-O were 1.610 « 0.001 ¡ and 1.531 « 0.005 ¡ in the examined range of the P 2 O 5 /SiO 2 ratio. More than 95% Si and P ions were 4-coordinated and formed tetrahedral structures. Average coordination numbers of P-O and Si-O decreased slightly while ave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 21 publications
2
15
0
Order By: Relevance
“…At variance with the RMC-SP model made of 100% Q 2 units, as expected for the NaPO 3 glass, , we note that models obtained by means of classical molecular dynamics are not so realistic as they contain sizeable fractions of Q 1 and Q 3 units. , In fact, the appearance of Q 1 and Q 3 is intrinsically related to the CMD atomistic description based on simple interaction potentials. , Moreover, the presence of Q 5 units is also likely to be an artifact of classical molecular dynamics. , Although we are not aware of any experimental data about Q 5 units in alkali phosphate glasses, we remark that Q 5 units might appear in melt phases . However, from a macroscopic dielectric point of view, the presence of a few Q 1 , Q 3 , and Q 5 units in CMD-SP does not substantially alter its dielectric response.…”
Section: Resultsmentioning
confidence: 73%
See 1 more Smart Citation
“…At variance with the RMC-SP model made of 100% Q 2 units, as expected for the NaPO 3 glass, , we note that models obtained by means of classical molecular dynamics are not so realistic as they contain sizeable fractions of Q 1 and Q 3 units. , In fact, the appearance of Q 1 and Q 3 is intrinsically related to the CMD atomistic description based on simple interaction potentials. , Moreover, the presence of Q 5 units is also likely to be an artifact of classical molecular dynamics. , Although we are not aware of any experimental data about Q 5 units in alkali phosphate glasses, we remark that Q 5 units might appear in melt phases . However, from a macroscopic dielectric point of view, the presence of a few Q 1 , Q 3 , and Q 5 units in CMD-SP does not substantially alter its dielectric response.…”
Section: Resultsmentioning
confidence: 73%
“…52,60 Moreover, the presence of Q 5 units is also likely to be an artifact of classical molecular dynamics. 61,62 Although we are not aware of any experimental data about Q 5 units in alkali phosphate glasses, we remark that Q 5 units might appear in melt phases. 63 However, from a macroscopic dielectric point of view, the presence of a few Q 1 , Q 3 , and Q 5 units in CMD-SP does not substantially alter its dielectric response.…”
Section: Sodium Phosphate Glass Models: Structuralmentioning
confidence: 89%
“…where X ðMOÞ represents the mole fraction of MO in molten slag. K P is the equilibrium constant of Reaction (8). C PO 3À 4 can be calculated with Equation ( 10) and (11).…”
Section: Thermodynamic Analysis Of the Effect Of Initial P Content In The Hot Metal On Dephosphorizationmentioning
confidence: 99%
“…There were some reports on the effect of the P 2 O 5 content in slag on the viscosity and microstructure of molten slag. [3][4][5][6][7][8][9][10] For example, Wang et slag increase. [10] Sun et al also reported that the viscosities of CaO-SiO 2 -Al 2 O 3 -MgO-TiO 2 -P 2 O 5 slags with the basicity of 0.5-0.97 increase substantially with increasing the P 2 O 5 addition amounts, in which P 2 O 5 acts as a characteristic network former in the melts.…”
Section: Introductionmentioning
confidence: 99%
“…They do, however, collectively suggest prospects of good correlations between structural characteristics and slag viscosity. Others have also used MD simulations to elucidate structural features like pair distribution functions (PDFs) and bond/bridging angles between atoms [18][19][20]. Such common structural characteristics may be related to the viscosity of slags because they contain attributes that reflect aspects of atomic mobility in the silicate network.…”
Section: Introductionmentioning
confidence: 99%